2020
DOI: 10.3390/ijerph17103551
|View full text |Cite
|
Sign up to set email alerts
|

Why are Spanish Adolescents Binge Drinkers? Focus Group with Adolescents and Parents

Abstract: Binge drinking in adolescents is a worldwide public healthcare problem. The aim of this study was to explore the perceptions about determinants of binge drinking in Spanish adolescents from the perspective of adolescents and parents. A qualitative study using fourteen semi-structured focus groups of adolescents was conducted during the 2014/2015 school year (n = 94), and four with parents (n = 19), based on the I-Change Model for health behaviour acquisition. Students had a low level of knowledge and risk perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
3
13
1
3
Order By: Relevance
“…No differences were detected in the consumption of alcohol between men and women, which confirms that alcohol consumption can no longer be largely associated with men, as previous studies have shown, and is now equally prevalent in both sexes [18,[55][56][57]. Neither were any differences found in the consumption of alcohol according to area of study, which seems to indicate that, among students of degrees within the field of health sciences, the choice of future profession has no bearing on alcohol consumption.…”
Section: Discussionsupporting
confidence: 81%
“…No differences were detected in the consumption of alcohol between men and women, which confirms that alcohol consumption can no longer be largely associated with men, as previous studies have shown, and is now equally prevalent in both sexes [18,[55][56][57]. Neither were any differences found in the consumption of alcohol according to area of study, which seems to indicate that, among students of degrees within the field of health sciences, the choice of future profession has no bearing on alcohol consumption.…”
Section: Discussionsupporting
confidence: 81%
“…Specially, binge drinking, more than marijuana use, seems to be related to low parental supervision and the absence of parent. This finding is interesting and may be related to the common use of alcohol among parents at home and with their low perception of risks in using it ( Martínez-Montilla et al, 2020 ). Indeed, parental drinking is associated with more probability to become a drinker in adolescence and adulthood ( De Looze et al, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…For instance, the abuse of marijuana seems to be more linked to the relationships with parents, as shown by a comparison between frequent marijuana users and never or less frequent lifetime marijuana users, where the first category of users is more likely to perceive a lack of parental support ( De Looze et al, 2015 ). Binge drinking, instead, seems to be associated with less parental supervision and the absence of parent, the availability of alcohol at home, and parents who drink alcohol ( Martínez-Montilla et al, 2020 ). The Canadian Institute of Health Research and the Heart and Stroke Foundation of Canada ( De Looze et al, 2015 ) confirmed these results, showing an association between the frequency of alcohol consumption and parental drinking.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other authors highlight the importance of peer influences [ 11 , 17 ]. A weak relationship has been observed between gender and consumption with a higher prevalence of drug use among men in particular, with the exception of sedative hypnotics, where use is higher among women [ 7 , 8 , 18 ].…”
Section: Introductionmentioning
confidence: 99%